2017
DOI: 10.1371/journal.pone.0182777
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates myocardial ischemia-reperfusion injury via up-regulation of antioxidant enzymes

Abstract: The objective was to examine the protective effect of metformin (Met) on myocardial ischemia-reperfusion (IR) injury and whether the mechanism was related to the AMPK/ antioxidant enzymes signaling pathway. Rat Langendorff test and H2O2-treated rat cardiomyocytes (H9c2) were used in this study. Met treatment significantly improved left ventricular (LV) function, reduced infarct size and CK-MB release in comparison with IR group. Decreased TUNEL staining positive cells were also observed in IR+Met group ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Combination of three contributory factors: increased antioxidant enzyme activity, lower mitochondrial ROS production and reduction of post-ischaemic inflammation have been suggested as mechanisms of metformin action to ameliorate I/R damage (Cahova et al, 2015). Recently, metformin has been proposed to exert its protective effect through the AMPK/ antioxidant enzymes signalling pathway (Wang et al, 2017). Recently, metformin has been proposed to exert its protective effect through the AMPK/ antioxidant enzymes signalling pathway (Wang et al, 2017).…”
Section: Ghasemnejad-berenjimentioning
confidence: 99%
See 3 more Smart Citations
“…Combination of three contributory factors: increased antioxidant enzyme activity, lower mitochondrial ROS production and reduction of post-ischaemic inflammation have been suggested as mechanisms of metformin action to ameliorate I/R damage (Cahova et al, 2015). Recently, metformin has been proposed to exert its protective effect through the AMPK/ antioxidant enzymes signalling pathway (Wang et al, 2017). Recently, metformin has been proposed to exert its protective effect through the AMPK/ antioxidant enzymes signalling pathway (Wang et al, 2017).…”
Section: Ghasemnejad-berenjimentioning
confidence: 99%
“…Ge et al (2017) demonstrated that Akt-mediated down-regulation of the phosphorylation of JNK3 signalling pathway contributed to the protection provided by metformin in hippocampus against ischaemic damage related to I/R injury. Recently, metformin has been proposed to exert its protective effect through the AMPK/ antioxidant enzymes signalling pathway (Wang et al, 2017). A number of reports also support the cardioprotective effect of metformin against myocardial infarction through AMPK-eNOS-mediated signalling pathway (Calvert et al, 2007) and adenosine receptor activation (Paiva et al, 2009).…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…C. elegans AMPK responds to nutritional state and coordinates hypoxia resistance (LaRue 101 and Padilla, 2011). These results translate to mammalian models, as AMPK protects against hypoxic 102 pathologies like ischemic reperfusion injury (Wang et al, 2017, Kim et al, 2011. In addition, AMPK acts as a 103 neuronal energy sensor capable of changing an animal's behavior based on food availability (Ahmadi and Roy, 104 2016, Yurgel et al, 2019).…”
mentioning
confidence: 97%